Metodika opredelenija veliciny trenirovocnych nagruzok junych chokkeistov - Nikitushkin, V. G.; Bodrov, V. Yu. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The purpose of the study is to determine the magnitude and annual volume of training loads of young hockey players aged 10-12 years old. The article outlines the current trends in the types of training of young hockey players, and discusses the problem of individualizing the training loads, based on the power zones, adopted in the domestic sports physiology, in which the certain physical exercises are performed. Research Objectives: 1. The study of practical materials of trainers of sports schools and schools of the Olympic reserve for this sport. 2. The construction of the training process based on the optimal training and competitive volumes of various training aids for young hockey players of the initial training groups. Based on the knowledge of the annual volumes and values of the training loads of young hockey players 10-12 years old, it seems possible to give practical recommendations to the coaches of the teams regarding the training of young hockey players. These recommendations are able to bring the team to high sports results in the further stages of preparation.